Dollarization of the Banking System : Good or Bad? - De Nicolo, Gianni (IMF Working Papers; Working Paper ;, 2003)
This paper assesses the benefits and risks associated with dollarization of the banking system. We provide novel empirical evidence on the determinants of dollarization, its role in promoting financial development, and on whether dollarization is associated with financial instability. We find that: (a) the credibility of macroeconomic policy and the quality of institutions are both key determinants of cross-country variations in dollarization; (b) dollarization is likely to promote financial deepening only in a high inflation environment; and (c) financial instability is likely higher in dollarized economies. The implications of these findings for financial sector and monetary policies are discussed.